Heck-type olefination and Suzuki coupling reactions using highly efficient oxacalix[4]arene wrapped nanopalladium catalyst - Manthan Panchal; Anita Kongor; Viren Mehta; Manoj Vora; Keyur Bhatt; Vinod Jain (Journal of Saudi Chemical Society, 2018)
A simple one-pot method is used for the synthesis of water dispersible and stable palladium nanoparticles (PdNps) where oxacalix[4]arene dihydrazide (OXDH) is used as both a reducing and capping agent. The OXDH-PdNps have been characterized by UV–Visible spectroscopy, Fourier transform infrared (FT-IR), transmission electron microscopy (TEM), energy‐dispersive X‐ray spectroscopy (EDX), powder X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The OXDH-PdNps are spherical in shape with an average size of 3–4 nm and well crystallized in a face centered cubic structure. The capping of the OXDH ligand on the nanoparticles surface was evaluated using FT-IR. The OXDH-PdNps have been used in carbon–carbon coupling reactions, namely, the Suzuki–Miyaura and Mizoroki–Heck reactions. Both of the reactions are carried out under phosphine-free conditions to provide better yields. The nanocatalyst can be easily recovered and reused for six consecutive catalytic cycles without any significant loss in its catalytic activity. Keywords: Palladium nanoparticles, Oxacalixarene, Suzuki–Miyaura’s reaction, C-C cross coupling reaction, Heck reaction